Investigating the urban heat island effect with the use of spatially explicit models in tropical cities - Chai, Min Wei (Nanyang Technological University, 2021)
Understanding urban heat islands has become vital for cities to adapt to a warming world. Much of the current urban heat studies are focused on temperate regions although there is a strong incentive for research in tropical cities, in particular in Southeast Asia, given the projections of high urban growth in the region. This project aims to bridge this gap by providing a workflow for running a spatially explicit model representing the distribution of air temperatures expected from a given Land Use/ Land Cover input. This project uses Singapore as its case study and involved the collection of data needed to run the model, calibration, and validation against observed air temperatures, and running an economic valuation analysis on future mitigation measures. This project will demonstrate the steps to apply the model to a new tropical city, the creation of future Land Use/ Land Cover scenarios based on existing urban planning strategies, and the use of the model to evaluate the effectiveness of future Land Use/ Land Cover scenarios. The gaps with each dataset will also be noted which can serve as future works and assist in future data collection.